The implementation of HIV/AIDS policies in local municipalities - a case study of Merafong city local municipality - Modiba, Khumo (My University, 2020)
The 2017-2022 National Strategic Plan is South Africa’s fourth generation Plan for HIV, TB and STIs since the polarised politicisation over suitable responses to the management of the epidemic. Over the years, AIDS policy planning has become relatively transparent and equally consultative among state and non-state actors. Despite this, policy analysis on this subject has predominantly been appraised at a national level with limited knowledge of how the Plan is operationalised at a subnational level, where implementation has proven to be the Achilles heel of policy. In this study, observational analyses together with interviews from a sample of eleven practitioners were conducted to consider how the National Strategic Plan cascades and translates into subnational plans, with a particular focus on Merafong City Local Municipality. The method of triangulation validated the congruence of document analysis with primary sources of data collected to ensure credibility and reliability. The findings indicate that the HIV/AIDS policy approach is top-down with NSP goals structuring implementation at the subnational level. However, challenges to implementation are attributed to weak AIDS council structures, a missing HIV/AIDS Coordinator, lack of political support for the HIV/AIDS programme, diminishing social behaviour change interventions which are attributed to a spike in risky sexual behaviour and the absence of an HIV/AIDS legislative framework to govern the country level response. Based on these results, the paper argues that the HIV/AIDS policy environment in Merafong hampers the development of a local plan and is not supportive of implementation that is responsive to the epidemic in the locality
A research report submitted in partial fulfilment of the degree of Master of Commerce (Development Theory and Policy) in the School of Economic and Business Sciences, University of the Witwatersrand, 2020